Síndrome de burnout en profesionales fisioterapeutas - Andrea Nataly, Hidalgo Zurita (2021)
ABSTRACT This project constitutes a bibliographic review, having as objective to analyze the prevalence of Burnout syndrome in physiotherapists. Through scientific evidence to improve the quality of life and the service provided by professionals. Burnout Syndrome is a pathology that occurs in workers with harmful psychosocial situations, the most affected are the health professionals. The beginning of burnout can occur during the academic phase; this is during the preparation period and continues during professional life. For evaluating this pathology, the Maslach Burnout Inventory (MBI) questionnaire is used; the characteristics are in three dimensions emotional exhaustion, depersonalization, and personal fulfillment. For the research methodology, 60 articles from different databases were analyzed, such as Scielo, Scopus, Proquest, PubMed, Elsevier, Dialnet, Researchgate. The found information was in different languages such as; English, Spanish, and Portuguese. Finally, “Physiotheraphy Evidence Database (PEDro)” Scale was to analyze the methodological quality that consists of eleven evaluation criteria and verify the validity and impact of the article, which as a result 35 articles for research development. At the end of the investigation, it concludes that Burnout syndrome is a pathology that is frequently found in physiotherapists due to various stress factors as a result of the workload that their work implies. Therefore, health professionals become more irritable, disappointed, and annoyed in the work environment. It is and is known for having bad attitudes and being apathetic. Keywords: Burnout syndrome, Physiotherapists, Maslach Burnout Inventory (MBI), exhaustion, work stress Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708